How, not just if, condoms are used: the timing of condom application and removal during vaginal sex among young people in England. Issue 1 (10th August 2006) - Hatherall, B; Ingham, R; Stone, N; McEachran, J
Abstract : Objective: To assess the prevalence of, and factors associated with, vaginal penetration before condom application and following condom removal among young people in education in England. Method: A large cross sectional survey (n = 1373) was conducted in educational establishments in England and sexual event diaries were completed by a subsample of young people over a 6 month period. Results: Of the 375 survey respondents who reported having used a condom on the most recent occasion of vaginal sex, 6% had applied the condom after penetration and 6% had continued penetration after condom removal. Of the 74 diary respondents, 31% applied a condom late and 9% removed a condom early at least once over a 6 month period. The odds of "imperfect" condom use were found to decrease with overall consistency of condom use, confidence in correct condom use, positive reported relationship with mother, non-use of other contraception, and desire to use a condom. Conclusion: Given that late application and early removal of condoms fail to maximise their effectiveness as a method of STI prevention, it is important to address "imperfect" condom use and the factors associated with such use in public health policies and programmes. It is essential that young people understand the importance of using condoms consistently and correctly, and are also equipped with the skills and knowledge to do so.